2020
DOI: 10.1093/cid/ciaa460
|View full text |Cite
|
Sign up to set email alerts
|

Profile of RT-PCR for SARS-CoV-2: A Preliminary Study From 56 COVID-19 Patients

Abstract: A novel coronavirus pandemic threatens the world. Here, we first studied the dynamics profile of SARS-CoV-2 from 56 recovered COVID-19 patients. We found virus shedding was up to 6 weeks after onset of symptoms. Prolonged observation period is necessary for older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
246
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(276 citation statements)
references
References 13 publications
(13 reference statements)
14
246
3
7
Order By: Relevance
“…The average VSPs were similar to those reported in the previous study [32]. After the multivariate linear regression analysis, we identi ed that disease durations at admission and HCQ/CQ treatment were independent parameters related to patients' VSPs, indicating patients might get better prognosis if being well treated earlier.…”
Section: Discussionsupporting
confidence: 83%
“…The average VSPs were similar to those reported in the previous study [32]. After the multivariate linear regression analysis, we identi ed that disease durations at admission and HCQ/CQ treatment were independent parameters related to patients' VSPs, indicating patients might get better prognosis if being well treated earlier.…”
Section: Discussionsupporting
confidence: 83%
“…As explained in (Harris 2020a), these parameters give a basic reproductive number at the start of the epidemic equal to . The value of implies a mean duration of infectivity of 20 days, considerably larger than some estimates, but more in line with other data (Wölfel et al 2020, Xiao, Tong, andZhang 2020).…”
Section: Appendix: Sir Modelssupporting
confidence: 87%
“…Some studies also reported that viral infectivity in patients with symptoms' duration > 8 days may be low [16,17]. Several factors might affect the occurrence of prolonged nucleic acid conversion, including older age, having comorbidities, such as diabetes and hypertension, and impaired immune function [18]. Our cases, except patient #1, had comorbidities, such as diabetes, hyperthyroid, asthma and arrhythmia.…”
Section: Discussionmentioning
confidence: 57%